2013
DOI: 10.1016/j.krcp.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

De novo glomerulitis associated with graft-versus-host disease after allogeneic hematopoietic stem cell transplantation: A single-center experience

Abstract: BackgroundNephrotic syndrome (NS) and proteinuria are uncommon, often unrecognized manifestations of graft-versus-host disease (GVHD) after hematopoietic stem cell transplantation (HSCT). Only a few isolated case reports and case series involving smaller number of patients who developed NS after HSCT have been published.MethodsWe reviewed the renal histopathological examination findings and clinical records of 15 patients who developed proteinuria after HSCT at Seoul and Yeouido St. Mary′s Hospital (Seoul, Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Anti-PLA2r antibodies have not been identified in MN suggesting that other antigens are likely to serve as antibody targets. [5][6][7] In MCD, T cell activation may be the cause of cytokine and antibody-mediated injury and can occur without other signs of GVHD, as evidenced in our patient. 8,9 The largest series of NS after GVHD was published by Reddy et al 10 who followed 889 patients and evaluated who developed non-cardiac edema with only 9 patients (0.9%) having evidence of NS.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Anti-PLA2r antibodies have not been identified in MN suggesting that other antigens are likely to serve as antibody targets. [5][6][7] In MCD, T cell activation may be the cause of cytokine and antibody-mediated injury and can occur without other signs of GVHD, as evidenced in our patient. 8,9 The largest series of NS after GVHD was published by Reddy et al 10 who followed 889 patients and evaluated who developed non-cardiac edema with only 9 patients (0.9%) having evidence of NS.…”
Section: Discussionsupporting
confidence: 53%
“…Minimal change disease was found in 15% of reports. 6 Similarly, Cho et al 7 reported in his cohort MN was the common glomerulopathy post HSCT. Anti-PLA2r antibodies have not been identified in MN suggesting that other antigens are likely to serve as antibody targets.…”
Section: Discussionmentioning
confidence: 80%
“…In idiopathic MN, PLA2R and thrombospondin type‐1 domain‐containing 7A (THSD7A), both expressed on podocytes, have been identified as autoantibody targets . In our cohort, as well as other series, anti‐PLA2R antibodies were not identified, suggesting that other antigens are likely to serve as antibody targets in MN post‐allo‐HSCT …”
Section: Case Series Of Nephrotic Syndrome After Allo‐hsct In the Litmentioning
confidence: 55%
“…Descriptions in the literature are limited to case reports and small case series. A literature search using the PubMed database with search terms ‘NS’, ‘renal failure’ and ‘haemopoietic transplant’ for publications in the English language since the year 2000 identified 10 case series (Table ) and 15 case reports, with a combined total of 67 cases. A pooled analysis was performed to identify key characteristics of this syndrome.…”
Section: Case Series Of Nephrotic Syndrome After Allo‐hsct In the Litmentioning
confidence: 99%
“…The most frequent renal histological finding was MN, followed by minimal change disease. Focal glomerulosclerosis, proliferative glomerulonephritis, and IgA nephropathy were also reported, although the numbers of cases were very small [1,27]. Our study suggests that proteinuria may be insidiously emerging and increasing within 1 year after SCT in nephrotic syndrome patients, and that hematologists or transplant physicians tend to understate its incidence.…”
Section: Discussionmentioning
confidence: 70%